(untitled) (Journal of the College of Education for Women, 2019)
E-Learning packages are content and instructional methods delivered on a computer(whether on the Internet, or an intranet), and designed to build knowledge and skills related toindividual or organizational goals. This definition addresses: The what: Training deliveredin digital form. The how: By content and instructional methods, to help learn the content.The why: Improve organizational performance by building job-relevant knowledge andskills in workers.This paper has been designed and implemented a learning package for Prolog ProgrammingLanguage. This is done by using Visual Basic.Net programming language 2010 inconjunction with the Microsoft Office Access 2007. Also this package introduces severalfacilities. Those facilities are represented in video lessons and their related websites viainternet as well as Google website, tests and administrator part for database manipulation.Keywords: Prolog, e-learning, database, Prolog’s syntax, Microsoft access database.